The Last Neighborhood Cops : the Rise and Fall of Community Policing in New York Public Housing. - Umbach, Fritz (Critical Issues in Crime and Society, 2011)
The Last Neighborhood Cops reveals the history of the residents and cops who forged community policing in the public housing complexes of New York City during the second half of the twentieth century. It draws on buried and confidential police records and voices of retired officers and older residents to help explore the rise and fall of the New York City Housing Authority Police Department's (HAPD) community-based strategy, while questioning its tactical effectiveness.